Perancangan Interior Pusat Terapi Dolphin Assisted Therapy (DAT) untuk Anak Autis di Surabaya - Elizabeth Stephanie; Sherly de Yong (Intra, 2019)
Autism is a developmental disorder in that causes children to have problems with their motoric sensors, and the number of autistic child has risen significantly. In order to help those children to develop better, some therapy is needed. One of them is a sensory therapy which works with dolphins, known as Dolphin Assisted Therapy, a therapy intended for autistic children, by swimming with dolphins as its main method. Through the concept of “Feel the Sea” and human center design method implemented in the interior design, not only swim and interact directly with the dolphins, parents and children are able to get underwater experience and also practicing their motoric sensors indirectly in each rooms provided.